Helpful Details for Commercial Propagation of Woody Plant Stem Cuttings - Thomas H. Yeager (EDIS)
This three-page fact sheet provides details that are very important for successful propagation of woody plant stem cuttings, such as sanitation, quality of cuttings, the time of year/day to take cuttings, stem size diameter and length of cutting, location of cuts/terminal bud removal, and environmental conditions. Written by Thomas Yeager and published by the Environmental Horticulture Department, December 2016.